Dialektika Islam dan Demokrasi (Pembacaan terhadap Syura Sebagai Elemen Demokrasi dalam Islam) - Tahir, Masnun (Fakultas Syariah IAIN Purwokerto, 2007)
Islam and democration are twoconcepts from the different culture entity. So when they are together they made a kind of trouble. It posibbly leads to a confict since they are confronted diametrically. Although it can be compromised substantially since there is a shura concept.